Lymphocyte subpopulations during cytomegalovirus disease in renal transplant recipients - S.M. Castro; H. Sporleder; R. Schröeder; A. Santos; V. Garcia; J. Neumann; S.C.B. Costa (Brazilian Journal of Medical and Biological Research, 2003)
We have determined the number of circulating T, B and natural killer cells in renal transplant recipients in order to detect changes during cytomegalovirus (CMV) infections. Serial blood samples were taken from 61 patients on standard triple immunosuppression therapy (cyclosporin A, azathioprine and prednisone). Using two-color flow cytometry analysis, the absolute number of CD3+, CD4+, CD8+, CD19+, CD3+HLA-DR+ and CD16+56+ cells was determined. Forty-eight patients (78.7%) developed active CMV infection, and all of them subsequently recovered. Twenty of the infected patients (32.8%) presented symptoms compatible with CMV disease during the infectious process. The number of lymphocytes and their main subpopulations were normal before the onset of CMV disease. During the disease there was a decrease followed by a significant increase (P<0.005) in the number of CD3+, CD4+, CD8+ and CD3+HLA-DR+ cells. No significant changes were observed in natural killer cells or B lymphocytes during the disease. We conclude, as observed in all viremic patients recovering from infection, that recovery is associated with an increase in the number of T cell subsets. The monitoring of different lymphocyte subsets along with antigenemia can be extremely useful in the detection of patients at high risk of developing CMV symptoms, allowing the early introduction of antiviral therapy or the reduction of immunosuppression therapy.